The Role of Food in the Family Relationships of Adolescents With Anorexia Nervosa and Bulimia in Northeastern Brazil: A Qualitative Study Using Photo Elicitation - Ramalho, Juniana de Almeida Mota; El Husseini, Mayssa'; Bloc, Lucas; Bucher-Maluschke, Julia Sursis Nobre Ferro; Moro, Marie Rose; Lachal, Jonathan (Frontiers in Psychiatry, 2021)
Family components can play roles both as protective factors and maintenance mechanisms of eating disorders. We aimed to investigate the role of food in the family relationships of adolescents with anorexia nervosa and bulimia in northeastern Brazil. Using photo elicitation, a visual narrative method that gives insight into the participants’ perspective through photograph, we conducted semi-structured interviews with 26 people: four teenage girls with anorexia, four with bulimia, eight mothers, four fathers, five grandmothers and one sister. Data were analyzed using the principles of Interpretative Phenomenological Analysis, which highlighted the following themes: control of the parent-adolescent relationship through food; food as means of experiencing parental presence-absence; food as a source of conflict in the nuclear family, and food as a source of three-generational conflict. Food seemed to be a mean for teens and parents to express physical suffering and psychological violence. Moreover, mourning appeared to influence the girls’ relationships with food. These families do not avoid conflict and teenagers’ emotional reactivity varied. These features reinforced the cultural aspect of eating experiences among adolescent girls with eating disorders. Remarkable disparities exist in the generations’ views on what rules and rituals these adolescents must follow at meals. These disparities can obfuscate generational boundaries in these families. Our data reinforce the need to focus on the adolescent's autonomy in the family setting and on family identity as related to food among three generations. These findings necessitate a reorganization of boundaries between these generations.